Is left atrial appendage isolation a pyrrhic victory in the effort to treat atrial fibrillation? - Bunch, T. Jared; Day, John D. (Journal of Thoracic Disease, 2017)
Atrial fibrillation (AF) in the majority of people is a chronic disorder that results in progressive scarring and fibrosis of the atrium (1). Since AF often reflects a long-term vascular disease state driven by obesity, sleep apnea, hypertension, and diabetes, drivers of progressive fibrosis often persistent even after starting rhythm control therapies (2).